Intelligent Space and its applications - Reskó, Barna; Niistuma, Mihoko; Baranyi, Péter; Korondi, Péter (Acta Agraria Kaposváriensis, 2007)
The spaces (rooms, buildings or offices) can be considered intelligent, in which the distributed, mutually communicating sensors not only passively records data, but can also understand it. The intelligent space can learn and recognize usual events. The purpose is to provide information or physical help to the inhabitants of the space, or to protect them from risks of unexpected events. The three main tasks of an intelligent space are sensing, processing and actuation. This paper gives an overview about research projects in the world about intelligent spaces, and presents the main activities and results of the Intelligent Integrated Systems Japanese – Hungarian Laboratory. One of the research projects deal with the so called spatial memory, which assigns functionalities to spatial points, providing a spatial user interface. The other important research topic is the application of cognitive vision in intelligent space, which aims to endow the space with visual abilities of mammalian animals. The final part of the paper gives a list of some potential fields of applications of Intelligent Space.
Keywords: Intelligent Space; spatial memory; cognitive vision